A kW-scale, 24-hour continuously operational, radiative sky cooling system: Experimental demonstration and predictive modeling. (15th April 2019) - Aili, Ablimit; Zhao, Dongliang; Lu, Jiatao; Zhai, Yao; Yin, Xiaobo; Tan, Gang; Yang, Ronggui
Highlights: A kW-scale day-night radiative sky cooling system is demonstrated. Daytime and nighttime cooling strategies based on optimum flow rates are investigated through modeling. Daytime and nighttime cold water generation tests are conducted. Predictive modeling of the system annual cooling performance is carried out. Abstract: With the advancement in sub-ambient cooling of water during daytime under the sun with scalable-manufactured radiative cooling metamaterials, the challenge for applications lies in design and building of large-scale radiative cooling systems. Here, we present a kW-scale, 24-hour continuously operational, radiative sky cooling system, with both experimental study and detailed modeling. We first quantitatively show how water flow rate directly affects the system cooling power and inversely affects the water temperature drop. A day-and-night stagnant (flow rate = 0 L/(min·m 2 )) water cooling test of the system shows a consistent sub-ambient water temperature drop of 5–7 °C. A daytime cooling test of the system at a low flow rate of 0.227 L/(min·m 2 ) yields a maximum sub-ambient temperature drop of 4.0 °C with an average net cooling power of around 80 W/m 2 . Further modelling for a typical metrological year (in Phoenix, Arizona) shows that the system could generate as much as 350 kWh cold (or 26 kWh/m 2 ) with a sub-ambient temperature drop of 4–5 °C at a low flow rate of 0.1 L/(min·m 2 ) during a typical summer month. The cold generated could be used to assist AC systems in regions or seasons with high ambient temperatures.